PEMBERDAYAAN GURU IPS SD DALAM PEMANFAATAN ARTIFICIAL INTELLIGENCE - M. Fashihullisan; Ahmad Hariyadi; Martini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence has become an unavoidable phenomenon. Likewise, the impact of artificial intelligence in the field of education has become a reality that schools and teachers must confront. Many teachers, particularly social studies teachers, are not yet prepared to cope with the advancement of artificial intelligence in educational processes. This study aims to analyze the attitudes of social studies teachers toward artificial intelligence in education and to examine strategies for empowering social studies teachers in utilizing artificial intelligence. The research method was a qualitative case study conducted with three elementary school teachers in Pati, Central Java, in May 2026. The findings reveal that all teachers participating in the study exhibited resistance toward the integration of artificial intelligence in social studies education. Consequently, an empowerment strategy based on a communicative action approach is required to strengthen teachers' capacity to effectively utilize artificial intelligence in the learning process.